2020
DOI: 10.1128/aac.02220-19
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of Monoclonal Antibodies Neutralizing Alpha-Hemolysin and Bicomponent Leukocidins in a Rabbit Model of Staphylococcus aureus Necrotizing Pneumonia

Abstract: Staphylococcus aureus is a major human pathogen that causes a wide range of infections by producing an arsenal of cytotoxins. We found that passive immunization with either a monoclonal antibody (MAb) neutralizing alpha-hemolysin or a broadly cross-reactive MAb neutralizing Panton-Valentine leukocidin, leukocidin ED, and gamma-hemolysins HlgAB and HlgCB conferred only partial protection, whereas the combination of those two MAbs conferred significant protection in a rabbit model of necrotizing pneumonia caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…It is interesting to note that several new treatments are in development against S. aureus infection including monoclonal antibodies aimed to neutralize S. aureus toxins [49]. In experimental animal models of infection in mice [50] and rabbits [51], the combination of monoclonal antibodies, including one targeting LukED, shows enhanced efficacy over single antibody administration with decreased bacterial burden [50] or increased survival [51]. In addition, new neutralizing agents called centyrins are able to block the binding of the five bicomponent leukocidins to their receptors and protect in vivo against S. aureus infection [52].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that several new treatments are in development against S. aureus infection including monoclonal antibodies aimed to neutralize S. aureus toxins [49]. In experimental animal models of infection in mice [50] and rabbits [51], the combination of monoclonal antibodies, including one targeting LukED, shows enhanced efficacy over single antibody administration with decreased bacterial burden [50] or increased survival [51]. In addition, new neutralizing agents called centyrins are able to block the binding of the five bicomponent leukocidins to their receptors and protect in vivo against S. aureus infection [52].…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that the addition of just one target with a bispecific antibody improves Hu-mAb efficacy [55,59,60]. Further, there are now pentavalent antibodies and mAb cocktails that are also being explored to improve efficacy [73,74]. One can certainly envision a future, 5-10 years from now, where there could be a Hu-mAb antibody product, cocktail or multivalent molecule, which is developed for each bacterial pathogen that causes difficult-to-treat infections.…”
Section: Future and Conclusionmentioning
confidence: 99%
“…More promising results by the Diep group came from two studies conducted in a NP rabbit model. The first study showed that passive immunization using a combination of an Hla-specific mAb (suvratoxumab) with a cross-neutralizing leukocidin mAb (SAN177 or SAN481) reduced mortality to 7% and 0%, respectively ( Figure 1 B) [ 195 ]. The second study showed similar results when attenuated Hla (Hla H35L/H48L ), combined with two attenuated PVL components (described in [ 88 ]), were used for active immunization [ 86 ], where 100% protection from lethality was observed in immunized rabbits ( Figure 1 C).…”
Section: Multicomponent Vaccinesmentioning
confidence: 99%
“…*: also neutralizes enterotoxins A and B and toxic shock syndrome toxin 1. (1): [ 193 , 194 ]; (2): [ 195 ]; (3): [ 86 ]; (4): [ 74 , 196 ]; (5): [ 197 , 198 ]; (6): [ 199 ]; (7): [ 200 ]; (8): [ 201 ]. (i): [ 202 ]; (ii): [ 203 ]; (iii): [ 204 ]; (iv): [ 183 ]; (v): [ 205 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation